2018
DOI: 10.1186/s12914-018-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the roles and capacities of duty bearers responsible for protecting the human rights to adequate food, nutritional health and wellbeing in Ugandan children’s homes

Abstract: BackgroundThe majority of Ugandan children face vulnerability and malnutrition. As a State Party to international human rights treaties, Uganda has legal obligations of guaranteeing the fundamental rights and the best interest of the nation’s children. Despite being protected under international and national law, Uganda is not providing adequate child protection, including safeguarding children’s food security. Numerous privately owned and unregulated children’s homes face this problem. The overall aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
2
4
0
3
Order By: Relevance
“…For instance, a study conducted in the United States reported violation of the human right to food in so far as mostly indigenous communities, people of color and those of lower socioeconomic backgrounds were struggling to put food on the table and were living paycheck to paycheck with limited support from the government [ 20 ]. Similarly a study in Uganda indicated that the state did not fulfil its obligation under the ICESCR to ensure children have their right to food and freedom from hunger [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study conducted in the United States reported violation of the human right to food in so far as mostly indigenous communities, people of color and those of lower socioeconomic backgrounds were struggling to put food on the table and were living paycheck to paycheck with limited support from the government [ 20 ]. Similarly a study in Uganda indicated that the state did not fulfil its obligation under the ICESCR to ensure children have their right to food and freedom from hunger [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This perception is held by a broad spectrum of community members including the young, the old, in-school and out of school children, men, and women. This view of children's rights as foreign continues to undermine advancement of child protection programs in Uganda (Ashukem, 2019;Katsui & Kumpuvuori, 2008;Olafsen et al, 2019), in Africa generally (London, 2017), and throughout the Third World (Cornwall & Nyamu-Musembi, 2004;Ife, 2012;London, 2017). To break through such strongly held beliefs, there is a need to integrate human rights with community engagement (London, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…La metodología de análisis de contenido tanto de instrumentos como de políticas fue una de las más utilizada entre los estudios incluidos en la presente revisión (7)(8)(9)12,13). Con relación a lo anterior, la aplicación de grupos focales y entrevistas semiestructuradas fueron técnicas realizadas en la mayoría de los estudios incluidos que buscaban explorar la percepción de diversos actores clave (16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionunclassified
“…Dos de los estudios que evaluaron el EBDH, uno realizado en Estados Unidos y otro en Uganda (16,17), encontraron desconocimiento del mandato y la autoridad del Ministerio de Agricultura y del Ministerio de Salud, como competentes responsables de garantizar el DHAA y la política de seguridad alimentaria, así como incumplimiento del EBDH para la buena gobernanza. Se encontró también una inadecuada incorporación de los instrumentos de monitoreo de DH ratificados en la legislación nacional, lo que indica una falta de compromiso del Estado y de cumplimiento de las normas de DH.…”
Section: Evaluación Del Dhaa Con Enfoque Basado En Derechos Humanos (...unclassified